Privileged scaffolds or promiscuous binders: a comparative study on rhodanines and related heterocycles in medicinal chemistry - Mendgen, Thomas; Steuer, Christian; Klein, Christian D. (Journal of medicinal chemistry, 2012)
Rhodanines and related five-membered heterocycles with multiple heteroatoms have recently gained a reputation of being unselective compounds that appear as “frequent hitters” in screening campaigns and therefore have little value in drug discovery. However, this judgment appears to be based mostly on anecdotal evidence. Having identified various rhodanines and related compounds in screening campaigns, we decided to perform a systematic study on their promiscuity. An amount of 163 rhodanines, hydantoins, thiohydantoins, and thiazolidinediones were synthesized and tested against several targets. The compounds were also characterized with respect to aggregation and electrophilic reactivity, and the binding modes of rhodanines and related compounds in published X-ray cocrystal structures were analyzed. The results indicate that the exocyclic, double bonded sulfur atom in rhodanines and thiohydantoins, in addition to other structural features, offers a particularly high density of interaction sites for polar interactions and hydrogen bonds. This causes a promiscuous behavior at concentrations in the “screening range” but should not be regarded as a general knockout criterion that excludes such screening hits from further development. It is suggested that special criteria for target affinity and selectivity are applied to these classes of compounds and that their exceptional and potentially valuable biomolecular binding properties are consequently exploited in a useful way.
Publication Date (Web): 14 November 2011
Gesehen am 28.11.2018